TASKS RELATED TO CONDUCT OF EXPERIMENT - Kukonboyeva, Shakhlo Rafikjonovna; Kukonboyev , Bakhodir Muqimovich; Ergasheva , Hurriyatkhan Melikoziyevna (Educational Research in Universal Sciences, 2023)
The article presents examples of tasks related to conducting experiments and the basis of their evaluation.